2023
DOI: 10.3389/fphar.2023.1265138
|View full text |Cite
|
Sign up to set email alerts
|

Ocular development after highly effective modulator treatment early in life

Yimin Zhu,
Danni Li,
Felisa Reyes-Ortega
et al.

Abstract: Highly effective cystic fibrosis (CF) transmembrane conductance regulator (CFTR) modulator therapies (HEMT), including elexacaftor-tezacaftor-ivacaftor, correct the underlying molecular defect causing CF. HEMT decreases general symptom burden by improving clinical metrics and quality of life for most people with CF (PwCF) with eligible CFTR variants. This has resulted in more pregnancies in women living with CF. All HEMT are known to be able pass through the placenta and into breast milk in mothers who continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…In people with CF (pwCF), the functionality of the CFTR protein is compromised in different ways depending on the mutation of the CFTR gene, there are more than 2000 variants that have been identified. ,, The defective or absent CFTR chloride channel results in the accumulation of chloride ions within the cell, and hyperabsorption of sodium. The altered cellular osmotic pressure increases the passive movement of water into the cell, leading to thicker and dehydrated mucus in the airway, resulting in impaired mucus clearance and decreased airflow. , The gastrointestinal tract (GIT), reproductive tract, sweat and salivary glands, and lungs of people with CF (pwCF) are affected and are usually characterized by chronic bacterial infection of the airways due to the CF patients commonly have dysregulated immunity and impaired mucus clearance. ,, The CFTR variants are traditionally categorized into 6 classes, and each class has a unique CFTR defect (Table ). Class I variants cause defective CFTR production, ultimately leading to the absence of the CFTR protein on the cell surface .…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…In people with CF (pwCF), the functionality of the CFTR protein is compromised in different ways depending on the mutation of the CFTR gene, there are more than 2000 variants that have been identified. ,, The defective or absent CFTR chloride channel results in the accumulation of chloride ions within the cell, and hyperabsorption of sodium. The altered cellular osmotic pressure increases the passive movement of water into the cell, leading to thicker and dehydrated mucus in the airway, resulting in impaired mucus clearance and decreased airflow. , The gastrointestinal tract (GIT), reproductive tract, sweat and salivary glands, and lungs of people with CF (pwCF) are affected and are usually characterized by chronic bacterial infection of the airways due to the CF patients commonly have dysregulated immunity and impaired mucus clearance. ,, The CFTR variants are traditionally categorized into 6 classes, and each class has a unique CFTR defect (Table ). Class I variants cause defective CFTR production, ultimately leading to the absence of the CFTR protein on the cell surface .…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…This condition may result from metabolic abnormalities in the course of CF. However, current research into new therapies for CF has also indicated an association between the use of CFTR protein modulators and an increased occurrence of lens opacification in the pediatric population [ 63 ].…”
Section: Lensmentioning
confidence: 99%
“…Similarly, cases of lens opacification in the pediatric population following ivacaftor, both as monotherapy and in combination, have also been reported. Data from published studies have shown that the incidence of cataracts in the pediatric population ranges from 0.57% to 4.17% [ 63 ].…”
Section: Lensmentioning
confidence: 99%
See 2 more Smart Citations